Occupational low-level exposure to hard metals: cobalt and tungsten biomonitoring as an effective tool to evaluate the effectiveness of industrial hygiene interventions for risk management. (17th February 2020) - Paganelli, M.; Fostinelli, J.; Renzetti, S.; Sarnico, M.; Tomasi, C.; Lovreglio, P.; Pilia, I.; Lecca, L. I.; De Palma, G.
Abstract: Purpose: The aim of the study was to assess the exposure to Cobalt (Co) and Tungsten (W) in a group of hard metal tool sharpeners through a combined approach of air and biological monitoring, and to evaluate the effectiveness of a control and improvement intervention carried out in collaboration with the medical officers of the local Health Protection Agency, by biomonitoring. Methods: We enrolled 132 workers from 17 companies of the province of Brescia, northern Italy. The study was performed in two phases: (1) an environmental and biomonitoring survey to assess the workers' exposure to Co and W at their usual working conditions; (2) a further biomonitoring survey 3 months after the enforcement of a control and improvement intervention, to assess its effectiveness. Results: Workers were found to be exposed to low concentration of airborne dust containing Co and W but after the intervention we recorded a significant decrease of the urinary concentrations of both Co and W. The extent of the decrease was correlated to the number of preventive industrial hygiene interventions that were carried out. Conclusions: Biological monitoring of Co and W in the hard metal tools manufacturing industry is a sensitive and effective method to evaluate the effectiveness of prevention practices.